MEDIA AUDIO VISUAL SEBAGAI SARANA KATEKESE OMK DI PAROKI SANTO PETRUS KANISIUS MANUFUI - Ukat, Kristophorus (STP St. Bonaventura Medan, 2019)
Audio visual media is one of the media that can be used to increase OMK's interest in catechesis. The purpose of this research is to increase the interest in catechesis of OMK, church life of OMK, and the importance of catechesis for OMK in Santo Petrus Kanisius Manufui Parish. While the method used in this research is field research method, including interviews related to audio-visual media in catechesis and distributing questionnaires to the OMK of Manufui Parish. The results showed that out of 40 respondents, 80% have understood the importance of audio visual media in catechesis, while out of 40 respondents, 20% have not understood what audio visual media is and the benefits of audio visual media in catechesis. This percentage is in the very good category, because most of the OMK have understood audio visual media as a means of increasing the interest of catechesis of OMK in church life at Santo Petrus Kanisius Manufui Parish very well